2015
DOI: 10.21273/horttech.25.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Biodegradation in Soil of Novel Horticulture Containers Made from Bioplastics and Biocomposites

Abstract: The container-crops industry relies heavily on single-use plant containers made from petroleum-based plastics, most of which contribute to the solid waste stream in landfills. Plant containers made from biorenewable materials have potential to be more sustainable, but most commercially available biocontainers are either not durable enough for common production cycles or do not effectively biodegrade in soil after use. In 2012 and 2013, we evaluated 28 novel biocontainers (injection-molded prototypes) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…Although some horticulturists have made efforts to recycle or reuse petroleum-based plastic containers, it is currently estimated that 98% of containers end up in the solid waste stream after only one use (Chappell and Knox, 2012;Kratsch et al, 2015). This practice results in the consumption and landfill disposal of more than 1 million tons of petroleum-based plastic in the form of horticulture containers each year in the United States (Schrader, 2013(Schrader, , 2016a.…”
mentioning
confidence: 99%
“…Although some horticulturists have made efforts to recycle or reuse petroleum-based plastic containers, it is currently estimated that 98% of containers end up in the solid waste stream after only one use (Chappell and Knox, 2012;Kratsch et al, 2015). This practice results in the consumption and landfill disposal of more than 1 million tons of petroleum-based plastic in the form of horticulture containers each year in the United States (Schrader, 2013(Schrader, , 2016a.…”
mentioning
confidence: 99%
“…TerraShell/OP47 (Summit Plastics), a wheat starch-based container with a minor PLA component (Nambuthiri et al, 2015), and SoilWrap (Ball Horticultural Co., West Chicago, IL, USA), a PHA-based bioplastic sleeve (Mohan, 2010), are the most commonly known commercial bioplastic plant containers. Growth and quality of plants produced TerraShell/OP47 or SoilWrap containers have been reported as similar to or greater than plants produced in petroleum-based plastic containers Kratsch et al, 2015;Villavicencio, 2010).…”
Section: Commercially Available Bioplastic Containersmentioning
confidence: 95%
“…Appearance of containers after multiple weeks in greenhouses has been reported as unchanged for both types of containers or similar to petroleum-based plastic containers (Kratsch et al, 2015;Villavicencio, 2010). Additionally, data on container biodegradation exist only for TerraShell/OP47 containers (Kratsch et al, 2015), and containers were reported as 3.1-10.3% degraded after 6 weeks in greenhouse crop production and 24 weeks buried in soil. A manufacturer of PLA-based plant containers has marketed bioplastic containers under the trade name TWBP-05 (Nanjing Beautystone Import & Export Co., Nanjing, China) though no research has been conducted using these containers or container quality.…”
Section: Commercially Available Bioplastic Containersmentioning
confidence: 97%
See 2 more Smart Citations